THE GENDER PERSPECTIVE AS A POLITICAL, THEORETICAL AND METHODOLOGICAL CONSTRUCT OF FEMINIST MATRIX - Maria da Silva, Salete (Revista Gênero e Interdisciplinaridade, 2025)
This text aims to contribute to the debate on the incorporation of a gender perspective in the legal field, especially in the context of training and/or qualifications for professionals in law and related areas who, after the advent of the Protocol for Judgment with a Gender Perspective (CNJ, 2021), have been required, since March 2023, to observe and implement its guidelines in all courts and instances of the Brazilian Judiciary. Its structure is divided into six topics, including the introduction and final considerations. The central argument revolves around the following questions: what is the gender perspective? Where does it come from? What is its relevance to the legal field? The answers to these questions enable not only the promotion of epistemic justice in favor of the feminist movement/thought from which the gender lenses emerge, but also a critical reflection on the challenges and possibilities of effectively adopting this perspective in the Brazilian justice system.